1990
DOI: 10.1128/iai.58.9.2862-2868.1990
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of suppressor T cell activity by the nontoxic lipopolysaccharide of Rhodopseudomonas sphaeroides

Abstract: Antibody responses of mice immunized with type III pneumococcal polysaccharide were examined with and without treatment with nontoxic lipopolysaccharide from Rhodopseudomonas sphaeroides (Rs-LPS). The results obtained were similar to those described previously for mice treated with monophosphoryl lipid A (MPL) except that lower amounts of Rs-LPS were needed. Both were without effect when given at the time of immunization with type III pneumococcal polysaccharide but elicited significant enhancement when given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Adeoye et al (2016) and Zhao et al (2018) found that intestinal microbiota, especially probiotics, played an important role in the nonspecific immune system, antioxidant system, and disease resistance and digestive system. Figure 2 and Jagielo et al (1998) and Baker et al (1990) support the finding that R. sphaeroides in effluent inhibited or killed pathogenic bacteria (Flavobacterium and Acinetobacter) and promoted the growth of probiotics in Common Carp intestine. Moreover, R. sphaeroides themselves were probiotics.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Adeoye et al (2016) and Zhao et al (2018) found that intestinal microbiota, especially probiotics, played an important role in the nonspecific immune system, antioxidant system, and disease resistance and digestive system. Figure 2 and Jagielo et al (1998) and Baker et al (1990) support the finding that R. sphaeroides in effluent inhibited or killed pathogenic bacteria (Flavobacterium and Acinetobacter) and promoted the growth of probiotics in Common Carp intestine. Moreover, R. sphaeroides themselves were probiotics.…”
Section: Discussionsupporting
confidence: 73%
“…Jagielo et al (1998) described that R. sphaeroides cell walls contained 3-hydroxy-sebacic acid and diphosphonic acid lipoid A. Baker et al (1990) observed that R. sphaeroides contained antiviral, antigen (Ag1, Ag2, Ag3), and immune factors and even secreted antibiotics. The above bioactive substances could inhibit or kill pathogenic bacteria (Baker et al 1990;Jagielo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of the antibody response to type III pneumococcal polysaccharide (SSS-III) is regulated in a negative and positive manner by the competitive interaction of thymus-derived CD8+ CD4suppressor T cells (Ts) and CD8-CD4+ amplifier T cells, respectively (reviewed in reference 2). Treatment with monophosphoryl lipid A (MPL) abolishes expression of Ts activity without adversely effecting expression of amplifier and helper T cell functions; this permits the positive effects of amplifier T cells on antigen-stimulated B cells to be more fully expressed, thereby resulting in either an increased antibody response to SSS-III or abrogation of Ts-mediated immunological unresponsiveness (6,7,13).…”
mentioning
confidence: 99%